Demographic Parameters of N’Dama Cattle Raised under Extensive Range Management Conditions in Southern Senegal - P. Ezanno (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux, 2002)
The aim of the present study was to describe demographic parameters of N’Dama cattle raised under extensive range management in Southern Senegal. The survey was conducted between 1993 and 1998. Calving, mortality, entry and exit events were individually recorded. Body condition was scored monthly for each cow over three years of age. Logistic regression models were fitted on a monthly scale to estimate the probabilities of pregnancy, mortality, and of entering and leaving the herd. The rate of pregnancy was related to the herd size, season and cow body condition. Except in the hot dry season, it was twice as high for cows scoring higher than 2.5 points for two consecutive months than for other cows. It was highest in the rainy season in large herds and in the cool dry season in smaller herds. Mortality decreased with age, with monthly adult mortality lower than 0.3%. Calf survival was related to milk availability, represented in the present study by variables concerning farmers’ practices (herd size), the environment and the dam (parity, calving body condition). Between birth and three years of age, monthly mortality ranged from 0.002 to 0.06. Entry and exit rates were higher in larger herds than in smaller ones, in which the main breeding objective was the herd demographic growth. Exchanges mainly occurred during the cool dry season.